New forms of marketing in the digital communication era - Lalević Nina B. (Megatrend Revija, 2022)
Marketing methods traditionally include psychological knowledge. In the Era of digital communication, marketing gained a neuro character, mostly thanks to EEG, fMRI, PET, eye tracking, facial coding, GSR, BVP, fNIRS, polygraph, TMS, indoor GPS etc. Marketing is still an assessment and decision prediction but now both directly and indirectly so to determine shopping preferences. Big industries like FMCG, fashion, automotive and so on, invest significant amount of money to make sure they know the needs and wishes of customers and in order to keep brand profitable. Shifting marketing to social media drastically changed strategies of global companies that are yet to see the outcome of this new approach of consumer involvement in PR. Likewise, the trend of consumer setting the tone of marketing caused gradual price correction and fabric procurement. Also, some number of consumers is especially interested in company's ecological awareness which includes best practice policy and a decision (not) to buy. That implies both on product and service. At the same time, in digital era, commercial is now subdued to comments, criticism and even boycott. Therefore, it's not uncommon for companies to have to hire PR machinery in order to solve the problem. New forms of marketing are subtle which doesn't mean that aggressive campaigns are gone for good, the ones that look more like propaganda that advertising. That is the basic marketing differentiation - is company nurturing an inbound or outbound/push or pull strategy. However, the dilemma remains; are companies really opening up for consumers to participate in their marketing campaign or is it a strategy of illusory influence that in fact represents a good marketing. In this paper, we analyze digital communication trends and social changes caused by rapid informatization of production, product and idea placement and sales.